MEMBANGUN LOYALITAS PELANGGAN MELALUI KUALITAS LAYANAN DAN COSTUMER SATISFACTION (Studi Pada Nasabah Pegadaian Syariah di Kota Bengkulu) - Herry Novrianda; Aan Shar (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
The rapid development of the financial industry in Indonesia has created opportunities for financial institutions to compete by enhancing service quality and customer satisfaction, aiming to foster customer loyalty. This research aims to investigate the influence of service quality and customer satisfaction, both partially and simultaneously, in building customer loyalty among Pegadaian customers in the city of Bengkulu. The sample comprises 127 Sharia Pegadaian customers in Bengkulu city selected through purposive sampling. The data analysis method employed is multiple linear regression analysis. The findings of this research indicate that service quality and customer satisfaction, both simultaneously and partially, have a positive and significant impact on customer loyalty. This implies that the better the services provided by the Sharia Pegadaian company in Bengkulu city, the more loyal customers become to the company. Similarly, high customer satisfaction leads to increased loyalty towards the Sharia Pegadaian company in Bengkulu city.